Induction of human cell DNA synthesis by herpes simplex virus type 2. - Melvin, P (1975)
The effect of herpes simplex virus type 2 (HSV-2) infection on the synthesis of DNA in human embryonic fibroblast cells was determined at temperatures permissive (37 C) and nonpermissive (42 C) for virus multiplication. During incubation of HSV-2 infected cultures at 42 C for 2 to 4 days or after shift-down from 42 to 37 C, incorporation of (3H)TdR into total DNA was increased 2-to 30-fold as compared with mock-infected cultures. Analysis of the (3H)DNA suggested that host cell DNA synthesis was induced by HSV-2 infection. Induction of host cell DNA synthesis by HSV-2 also occurred in cells arrested in DNA replication by low serum concentration. The three strains of HSV-2 tested were capable of stimulating cellular DNA synthesis. Virus inactivated by UV irradiation, heat, or neutral red dye and light did not induce cellular DNA synthesis, suggesting that an active viral genome is necessary for induction.